The raven's eye - Maitland, Barry (Maitland, Barry. Brock and Kolla novels., 2013)
DI Kathy Kolla of Scotland Yard is called in as a matter of course by the local Paddington police when a woman turns up dead in what appears to be an accident. On her houseboat, Vicky Hawks is found by one of her neighbors, having apparently succumbed to carbon monoxide poisoning due to improper ventilation of the narrowboat's heating system. But while the cause of death seems apparent and there's no reason for Kolla to think otherwise, something about this death still bothers her"--